Who sets the pace in robotisation? ‘Working at a robotic pace’ according to the justifying, criticising and problem-solving discourse frames - Turja, Tuuli (Human Technology, 2024)
In a society driven by clock time and technology, it is no suprise that a robotic working pace is often viewed as inevitable, even ideal. However, ultimately discussions regarding robotic pace are shaped by different perspectives and contexts. In this paper, content-frame analysis was used to examine how ‘working at a robotic pace’ is addressed in academic discourse across scientific disciplines. The statements (N=22) were coded and examined for their positive, negative, or neutral appraisal, as well as the value base derived from either a human(e) or efficiency perspective. In academic communication, the concept has been framed by justifying, criticizing, and problem-solving discourses. The criticising frame was not found exclusively in the social sciences but across disciplines. It was the most common discourse frame, with its subjective perspective focusing on people and well-being. The problem-solving frame included a neutral, constructive and more objective approach associated with socio-technical ideals emphasized in engineering disciplines.